2021
DOI: 10.3390/e23101314
|View full text |Cite
|
Sign up to set email alerts
|

Polar Vortex Multi-Day Intensity Prediction Relying on New Deep Learning Model: A Combined Convolution Neural Network with Long Short-Term Memory Based on Gaussian Smoothing Method

Abstract: The variation of polar vortex intensity is a significant factor affecting the atmospheric conditions and weather in the Northern Hemisphere (NH) and even the world. However, previous studies on the prediction of polar vortex intensity are insufficient. This paper establishes a deep learning (DL) model for multi-day and long-time intensity prediction of the polar vortex. Focusing on the winter period with the strongest polar vortex intensity, geopotential height (GPH) data of NCEP from 1948 to 2020 at 50 hPa ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…The definition of RMSE is shown in Equation ( 10 ). Determinable coefficient ( ) is a statistic that measures the goodness of fit [ 43 ]. is the ratio of the covariance of the two datasets to the standard deviation of the two datasets.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The definition of RMSE is shown in Equation ( 10 ). Determinable coefficient ( ) is a statistic that measures the goodness of fit [ 43 ]. is the ratio of the covariance of the two datasets to the standard deviation of the two datasets.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Previous studies used different statistical models to predict stratospheric variability and identify SSW events at timescales longer than 1 week, such as multiple linear regression (MLR) and fully connected neural networks (NNs), and found that a well-trained NN can exhibit promising skill in the prediction of SPV variations (e.g., Blume and Matthes, 2012; Peng et al, 2021). However, given the multiple variables with different lead times used in these studies and the nonlinear structure of NNs, the key factors and features that the NNs use to make the prediction are not clear.…”
Section: Motivationmentioning
confidence: 99%